Near-infrared spectroscopy monitoring during out-of-hospital cardiac arrest: can the initial cerebral tissue oxygenation index predict ROSC?. Issue 1 (16th November 2018) - Tsukuda, Jumpei; Fujitani, Shigeki; Morisawa, Kenichiro; Shimozawa, Nobuhiko; Lohman, Brandon D; Okamoto, Kentaro; Kawaguchi, Takeshi; Takamatsu, Yuka; Fujii, Shuichi; Ozaki, Masayuki; Rahman, Mahbubur; Taira, Yasuhiko
Abstract : Study objectives: Near-infrared spectroscopy is a modality that can monitor tissue oxygenation index (TOI) and has potential to evaluate return of spontaneous circulation (ROSC) during cardiopulmonary resuscitation (CPR). This study's objectives were to evaluate whether TOI could be associated with ROSC and used to help guide the decision to either terminate CPR or proceed to extracorporeal CPR (ECPR). Methods: In this observational study, we assessed the patients with out-of-hospital cardiac arrest with non-traumatic cause receiving CPR on arrival at our ED between 2013 and 2016. TOI monitoring was discontinued either on CPR termination after ROSC was reached or on patient death. Patients were classified into two groups: ROSC and non-ROSC group. Results: Out of 141 patients, 24 were excluded and the remaining 117 were classified as follows: ROSC group (n=44) and non-ROSC group (n=73). ROSC group was significantly younger and more likely to have their event witnessed and bystander CPR. ROSC group showed a higher initial TOI than non-ROSC group (60.5%±17.0% vs 37.9%±13.7%: p<0.01). Area under the curve analysis was more accurate with the initial TOI than without it for predicting ROSC (0.88, 95% CI 0.82 to 0.95 vs 0.79, 95% CI 0.70 to 0.87: p<0.01). TOI cut-off value ≥59% appeared to favour survival to hospital discharge whereas TOI ≤24% was associated with non-ROSC. Conclusions: This study demonstrated an association between higher initial TOI and ROSC. Initial TOI could increase the accuracy of ROSC prognosis and may be a clinical factor in the decision to terminate CPR and select patients who are to proceed to ECPR.